Hass avocado and profitability in the crisis: A critical look at Peruvian exports (2018–2022) - Capuñay Corthon, Mathias Eduardo; Díaz Mujica, Edita Jesús; Rivas Mendoza, Milagros Isabel (LACCEI, 2025)
The objective of this research was to determine the main problems affecting the export performance of Hass avocado in Peru during the period 2018–2022. A qualitative approach with a non-experimental, descriptive design was used, based on documentary review and comparative analysis of official export records. The results revealed that, although the export volume grew steadily—reaching over 550,000 tons in 2021—this growth did not translate into increased profitability. Key issues identified include excessive dependence on fresh fruit formats (over 96% of exports), limited access to value-added markets, high logistical costs, lack of cold chain infrastructure, and strong concentration of export destinations in the Netherlands and the United States. Additionally, the seasonality of harvests caused oversupply during peak months, pushing international prices down. These limitations were especially critical for small agricultural enterprises, which face barriers to meeting international standards. The study concluded that the current export model is volume-centered and vulnerable to market fluctuations.